Heterogeneous Parahydrogen Pairwise Addition to Cyclopropane. Issue 20 (7th August 2018) - Salnikov, Oleg G.; Kovtunov, Kirill V.; Nikolaou, Panayiotis; Kovtunova, Larisa M.; Bukhtiyarov, Valerii I.; Koptyug, Igor V.; Chekmenev, Eduard Y.
Abstract: Hyperpolarized gases revolutionize functional pulmonary imaging. Hyperpolarized propane is a promising emerging contrast agent for pulmonary MRI. Unlike hyperpolarized noble gases, proton‐hyperpolarized propane gas can be imaged using conventional MRI scanners with proton imaging capability. Moreover, it is non‐toxic odorless anesthetic. Furthermore, propane hyperpolarization can be accomplished by pairwise addition of parahydrogen to propylene. Here, we demonstrate the feasibility of propane hyperpolarization via hydrogenation of cyclopropane with parahydrogen. 1 H propane polarization up to 2.4 % is demonstrated here using 82 % parahydrogen enrichment and heterogeneous Rh/TiO2 hydrogenation catalyst. This level of polarization is several times greater than that obtained with propylene as a precursor under the same conditions despite the fact that direct pairwise addition of parahydrogen to cyclopropane may also lead to formation of propane with NMR‐invisible hyperpolarization due to magnetic equivalence of nascent parahydrogen protons in two CH3 groups. NMR‐visible hyperpolarized propane demonstrated here can be formed only via a reaction pathway involving cleavage of at least one C–H bond in the reactant molecule. The resulting NMR signal enhancement of hyperpolarized propane was sufficient for 2D gradient echo MRI of ∼5.5 mL phantom with 1×1 mm 2 spatial resolution and 64×64 imaging matrix despite relatively low chemical conversion of cyclopropane substrate. Abstract : Heterogeneous hydrogenation of cyclopropane with parahydrogen over a Rh/TiO2 catalyst is shown to be a promising approach for producing propane gas with a high level of proton polarization, suitable for magnetic resonance imaging applications.